Управление напряженным состоянием плоской многослойной катушки тороидального магнитного поля - Зайцев, Б. Ф.; Шульженко, Н. Г. (НТУ "ХПИ", 2001)
The possibility of reducing maximum stress in multilayer electromagnetic coils is considered. Optimum separation of conducting and nonconducting layers, which introduces the elastic support effect, is suggested. The finite-element method and the modified plane stress state scheme are applied.
Keywords: напряженность катушек; электромагнитное поле; удержание плазмы; подкрепляющие накладки; опирание катушки